Knowledge on Newborn Care among Primi Postnatal Mother in District Hospital Chitwan, Nepal (Global Journal of Medical Research, 2022)
Background The birth of a newborn is a blissful moment in one s life Newborn babies constitute the foundation of any nation It referred to a baby under 28 days of life During their first month of life these newborns undergo remarkable physical cognitive emotional psychological social sensory and motor skills development Worldwide around about three million newborns die in this period Neonatal mortality is a public issue in low and middle-income countries Knowledge of newborn care among mothers is important for the survival growth and development of a newborn Methods The objective of the study was to assess the knowledge of newborn care among primipostnatal mothers in the district hospital Chitwan A descriptive cross-sectional study design was adopted and 104 postnatal mothers were selected using a non-probability convenient sampling technique Data were collected by using interviews Data entry was done by using Epi data and analysed by SPSS Descriptive and inferential statistics were used to analyze the collected data
Keywords: knowledge; newbor; care; postnatal; primi mother